TOURISM BASED PEOPLE'S ECONOMY IN ORDER TO IMPROVE THE COMMUNITY'S ECONOMY - Dian Marlina Verawati; Sudati Nur Sarfiah; Hanung Eka Atmaja (Riset Ekonomi Pembangunan, 2021)
Magelang Regency has so many interesting tourism places to visit. The tourism sector is one of the sectors that has the potential to improve the people's economy. One of the most popular tourist attractions is Borobudur Temple. Development of people’s economy-based tourism can improve the welfare of the community around tourist sites. With the growth of tourism, it will be linearly proportional to the growth of the surrounding MSMEs. This populist economy-based tourism means tourism based on the economic strength of the people in the form of businesses or community groups altogether to process economic resources that can contribute to the welfare of local communities. The purpose of this study is to provide an overview of populist economy-based tourism in Magelang Regency. The research method uses a qualitative descriptive method based on literature review and a literature approach on the phenomenon of tourism in developing the people's economy in Magelang Regency in 2017 - 2019, with a case study on a tourist spot, namely the Borobudur Temple. The results showed that the development of populist economy-based tourism gave rise to many MSMEs and could improve the economy of the people around the tourism sites in Magelang Regency.